2014
DOI: 10.1007/s10557-014-6553-6
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Obese-Insulin Resistance and Anti-Diabetic Drugs on the Heart with Ischemia-Reperfusion Injury

Abstract: The incidence of obesity with insulin resistance is increasing worldwide. This condition is also known as a risk factor of coronary artery disease and associated with increased arrhythmias, impaired left ventricular function, and increased infarct size during cardiac ischemia-reperfusion (I/R) injury. The proposed mechanisms are due to impaired glucose utilization and pro-survival signaling molecules, and increased inflammatory cytokines, which have been demonstrated in the I/R hearts in various models of obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…MIR injury is characterized by oxidative stress, activation of apoptosis pathways, and enlargement of infarct size, which significantly contributes to long‐term mortality and heart failure post‐MI . Preexisting myocardial hypertrophy and glycemic dysregulation significantly exacerbate MIR injury . Of note, infants born to diabetic mothers are prone to develop myocardial hypertrophy, and increased prevalence of glucose intolerance or diabetes in adult offspring of diabetic pregnancy was reported, suggesting diabetic mother offspring may be more vulnerable to MIR injury, although further investigation is required.…”
Section: Introductionmentioning
confidence: 99%
“…MIR injury is characterized by oxidative stress, activation of apoptosis pathways, and enlargement of infarct size, which significantly contributes to long‐term mortality and heart failure post‐MI . Preexisting myocardial hypertrophy and glycemic dysregulation significantly exacerbate MIR injury . Of note, infants born to diabetic mothers are prone to develop myocardial hypertrophy, and increased prevalence of glucose intolerance or diabetes in adult offspring of diabetic pregnancy was reported, suggesting diabetic mother offspring may be more vulnerable to MIR injury, although further investigation is required.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in contrast with the many well-established age-related modifications in the cardiovascular system [13], but it should be kept in mind that our observations were made in healthy animals, without the comorbidities which may affect the outcome. There is also continued interest in the ability of cardioprotective interventions such as pre-or postconditioning to protect the ageing myocardium [14]. Our data showed that although aging hearts exhibited normal function under baseline conditions, with an unchanged response to I/R and retention of the capacity to reduce infarct size when preconditioned, this was associated with a reduction in the ability to recover functionality.…”
Section: Discussionmentioning
confidence: 75%
“…Possible signalling mechanisms involved in the effects of obese-insulin resistance have been reviewed by Apaijai and coworkers [4]. Unfortunately, as was the case in the outcome of the effects of I/R, no clear-cut pattern of changes emerged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations